Lipid droplets in Arabidopsis thaliana leaves contain myosin-binding proteins and enzymes associated with furan-containing fatty acid biosynthesis - Omata, Yuto; Sato, Reina; Mishiro-Sato, Emi; Kano, Keiko; Ueda, Haruko; Hara-Nishimura, Ikuko; Shimada, Takashi L. (Frontiers in Plant Science, 2024)
Ahead of submission, you should prepare a statement summarizing in 200 words your manuscript's contribution to, and position in, the existing literature of your field. This should be written avoiding any technical language or non-standard acronyms. The aim should be to convey the meaning and importance of this research to a non-expert. (Note that you will NOT be able to provide a traditional cover letter.) Lipid droplets (LDs) are lipid storage organelles in plant seeds and leaves. Although some leaf LD proteins are known to function in lipid metabolism, many remain to be identified and characterized. Here, we conducted LD proteomics using a leaf LD-overaccumulating mutant of Arabidopsis thaliana. We detected thousands of proteins by mass spectrometry, including 3,206 candidate leaf LD proteins. We focused on seven previously unreported LD proteins: five myosin-binding proteins and two uncharacterized proteins. Notably, we observed LD movement along the actin filament, suggesting that the myosin-binding proteins facilitate LD movement. The two uncharacterized proteins were highly similar to enzymes for furan-containing fatty acid biosynthesis in the photosynthetic bacterium Cereibacter sphaeroides. Biosynthesis of furan-containing fatty acids in plants is largely unknown; however, our results suggest that these two proteins may be involved in furan-containing fatty acid biosynthesis in LDs, providing insight into the physiological and molecular functions of leaf LDs. Analysis of this small subset of candidate proteins indicates that our proteome data are a valuable resource for mining other unidentified LD proteins. In addition, our LD proteomics method will be useful for investigating LDs in other systems.